2018
DOI: 10.1051/0004-6361/201833913
|View full text |Cite
|
Sign up to set email alerts
|

Shadows and asymmetries in the T Tauri disk HD 143006: evidence for a misaligned inner disk

Abstract: Context. While planet formation is thought to occur early in the history of a protoplanetary disk, the presence of planets embedded in disks, or of other processes driving disk evolution, might be traced from their imprints on the disk structure. Aims. We study the morphology of the disk around the T Tauri star HD 143006, located in the ∼5-11 Myr-old Upper Sco region, and we look for signatures of the mechanisms driving its evolution. Methods. We observed HD 143006 in polarized scattered light with VLT/SPHERE … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
114
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(122 citation statements)
references
References 95 publications
8
114
0
Order By: Relevance
“…This hinted toward significantly misaligned inner disc components and/or the need for other dipper mechanisms. Evidence of misaligned inner discs has also been recently inferred for several systems using high-contrast optical/infrared images, which have revealed shadows in the outer disc cast by unseen inclined inner disc components (e.g., Marino et al 2015;Stolker et al 2016;Debes et al 2017; Benisty et al 2018;Casassus et al 2018). A notable example is the dipper J1604, which hosts a face-on transition disc resolved by ALMA (Ansdell et al 2016a) and variable shadows seen by VLT/SPHERE (Pinilla et al 2018a), suggesting a highly misaligned (∼70-90 • ) and dynamic inner disc component.…”
Section: Introductionmentioning
confidence: 82%
“…This hinted toward significantly misaligned inner disc components and/or the need for other dipper mechanisms. Evidence of misaligned inner discs has also been recently inferred for several systems using high-contrast optical/infrared images, which have revealed shadows in the outer disc cast by unseen inclined inner disc components (e.g., Marino et al 2015;Stolker et al 2016;Debes et al 2017; Benisty et al 2018;Casassus et al 2018). A notable example is the dipper J1604, which hosts a face-on transition disc resolved by ALMA (Ansdell et al 2016a) and variable shadows seen by VLT/SPHERE (Pinilla et al 2018a), suggesting a highly misaligned (∼70-90 • ) and dynamic inner disc component.…”
Section: Introductionmentioning
confidence: 82%
“…When the misalignment between the inner and outer components is large, twin narrow shadows are cast on the surface of the outer disk (Avenhaus et al 2014;Marino et al 2015). For small misalignments, however, when the relative inclination between components is only of a few degrees, a single broad shadow is cast (Juhász & Facchini 2017;Debes et al 2017;Benisty et al 2018). The shape of the asymmetry of the outer disk, with the fainter region of the disk appearing roughly constrained to a constant range of PAs between ∼0 • and 240 • (see Fig.…”
Section: Motivationmentioning
confidence: 99%
“…Numerous radial and azimuthal features such as spirals (Benisty et al 2015(Benisty et al , 2017Pérez et al 2016;Huang et al 2018), shadows (Avenhaus et al 2014;Stolker et al 2016;Benisty et al 2018), gaps (ALMA Partnership et al 2015;Tsukagoshi et al corresponding author: cuellonicolas@gmail.com 2016; Dipierro et al 2018;Andrews et al 2018), warps (Langlois et al 2018;Casassus et al 2018;van der Plas et al 2019), horseshoes (van der Marel et al 2013;Boehler et al 2017), and clumps (Dong et al 2018;Gratton et al 2019) have been reported. Such structures are potential signposts of disc-companion interactions (Dong et al 2015;Price et al 2018b;Poblete et al 2019;Calcino et al 2019, for instance).…”
Section: Introductionmentioning
confidence: 99%